2022
DOI: 10.1029/2022gl101232
|View full text |Cite
|
Sign up to set email alerts
|

Deducing Lunar Regolith Porosity From Energetic Neutral Atom Emission

Abstract: The surfaces of airless bodies are covered by a porous regolith, a loose ensemble of rocks and dust grains, due to a multitude of erosion and impact processes over billions of years (McKay et al., 1991). Its upper layers determine how those planetary bodies are observed as their surface morphology strongly affects optical properties (Hapke, 2008;Vernazza et al., 2012). The porous structure of stacked grains will also influence the interaction of any planet, moon, or asteroid with its environment or precipitati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
37
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(43 citation statements)
references
References 76 publications
6
37
0
Order By: Relevance
“…With our model (Szabo et al, 2022b), we have previously shown that the total backscattering coefficient depends on regolith porosity, reproducing Chandrayaan-1 data for its angular dependence with fairy-castle like, highly porous regolith. Ultimately, the lunar regolith porosity at the surface could be constrained to 𝐴𝐴 0.85 +0.15 −0.14 .…”
supporting
confidence: 78%
See 2 more Smart Citations
“…With our model (Szabo et al, 2022b), we have previously shown that the total backscattering coefficient depends on regolith porosity, reproducing Chandrayaan-1 data for its angular dependence with fairy-castle like, highly porous regolith. Ultimately, the lunar regolith porosity at the surface could be constrained to 𝐴𝐴 0.85 +0.15 −0.14 .…”
supporting
confidence: 78%
“…We tested the sensitivity of the scattering function on regolith parameters by running one simulation with a lower porosity of around 0.5 and one simulation for irregular grain shapes, which were created with a fractal dimension f d = 2.6 using an algorithm proposed by Wei et al (2018) in the same manner as it was done in Szabo et al (2022b). Plots of these simulation results are given in Supporting Information S1, but the differences to the high-porosity, spherical-grain case presented here are minor.…”
Section: Ena Scattering Anglesmentioning
confidence: 99%
See 1 more Smart Citation
“…Because the cosine distribution of incidence angles approximates the variation in impact angles and corresponding yields expected for a spherical grain surface, it is considered the best approximation currently available within SDTrimSP for SW interactions with regolith. More recent research has also shown that an upcoming 3D version of SDTrimSP could provide another option to capture the granular surface profile (Szabo et al 2022b). Previous research has suggested that ion sputtering of regolith due to normally incident SW can be distinctly different than ion sputtering from a Figure 2.…”
Section: Effect Of Impact Anglementioning
confidence: 99%
“…In recent years there were several efforts to better constrain the erosion of rocky planetary bodies exposed to highly energetic solar wind ions. This includes investigating the effect of surface roughness (Biber et al 2022) and porosity (Szabo et al 2022b), performing ion irradiation experiments with mass yield measurements (e.g., Hijazi et al 2017;Szabo et al 2018Szabo et al , 2020aBiber et al 2022), and introducing a new surface and bulk binding energy (BBE) model from theory (Hofsäss & Stegmaier 2022;Morrissey et al 2022). In this work, we discuss the parameter of density and its inclusion in SDTrimSP (Mutzke et al 2019), as well as a new hybrid binding energy model that reliably recreates experimental sputter yields completely without the requirement to adjust input parameters.…”
Section: Introductionmentioning
confidence: 99%